PENINGKATAN MOTIVASI BELAJAR PESERTA DIDIK MELALUI PROBLEM BASED LEARNING PATA MATA PELAJARAN BIOLOGI KELAS X SMAN 1 KETUNGAU HULU - JOHNLI ALFATH (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2023)
The purpose of this study was to increase students' learning motivation through a problem-based learning model in biology class X MIA SMAN 1 Ketungau Hulu. The subjects of this study were 35 class X MIA students at SMAN 1 Ketungau Hulu. This research is a classroom action research with two cycles. Based on the data analysis and discussion in IV, it can be concluded that the use of the PBL model can increase students' learning motivation in the material